FREQUENCY OF FOLIC ACID DEFICIENCY IN WOMEN OF CHILDBEARING AGE PRESENTING AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Saqib Malik; Zainab Syed; Farhat Naz; Rehman, Najma; Sadia Rehman; Talha Durrani (Journal of Ayub Medical College Abbottabad, 2022)
Background: Folic acid deficiency is one of the most common deficiencies among women of childbearing age. It can lead to neural tube defects, a significant cause of disability and mortality among infants. Therefore, the main objective of this study was to determine a folic acid deficiency in women of childbearing age in Ayub Teaching Institute, Abbottabad Methods: This cross-sectional study was carried out in Ayub Teaching Institute, Abbottabad from January 2020 to June 2020. In this study, a total of 193 women of childbearing age were included through consecutive sampling. Results: In this study 193 women of childbearing age were included. Mean age was 30±4.87 years. Out of 193 patients, 56.7% were found to be anemic and 38.9%were found to have folic acid deficiency. Conclusion: Our study concludes that the majority of women of child bearing age are anemic in our set up. Moreover, the frequency of folic acid deficiency is 38.9 % which is high.